Seasonal Changes and Habitat Influencing Helminthiasis in Bobwhite Quail - M. F. Hansen; R. J. Robel (National Quail Symposium Proceedings, 2017)
Two hundred forty-four bobwhite quail (Colinus virginianus) were collected in Kansas and examined for helminths during 1963-1966. Total incidence of helminthic infection was 23%; 24% in juveniles and 22% in adults. Total incidence of nematode infection was 13%, cestodes, 10% and no trematodes were recovered. Six species of nematodes, 1 species of cestode, and 1 species of acanthocephalan were found in the quail examined. Peak incidence of infection occurred from September to November during the 3- yr study .. Incidence of infection was greater during February-April 1965, than during similar periods of 1964 and 1966. Bobwhites collected within 0.5 mile of farms with poultry had a helminthic incidence of 38%, whereas, those collected 1.5 miles or more removed from farms with poultry had an incidence of only 8%, suggesting that poultry may be serving as a reservoir of helminthic infection for wild bobwhites.